Il gioco del killer Culture mafiose e minori - CAVA, ANTONIA (Scienze della Comunicazione - Open Access, 2020)
This volume collects the contributions of scholars who analyze mafia cultures and juvenile deviance generating a close comparison between different theoretical and research perspectives.